Your ticket to independence: a guide to getting your first Principal Investigator position. (October 2015) - Káradóttir, Ragnhildur Thóra; Letzkus, Johannes J.; Mameli, Manuel; Ribeiro, Carlos
Abstract The transition to scientific independence as a principal investigator (PI) can seem like a daunting and mysterious process to postdocs and students ‐ something that many aspire to while at the same time wondering how to achieve this goal and what being a PI really entails. The FENS Kavli Network of Excellence (FKNE) is a group of young faculty who have recently completed this step in various fields of neuroscience across Europe. In a series of opinion pieces from FKNE scholars, we aim to demystify this process and to offer the next generation of up‐and‐coming PIs some advice and personal perspectives on the transition to independence, starting here with guidance on how to get hired to your first PI position. Rather than providing an exhaustive overview of all facets of the hiring process, we focus on a few key aspects that we have learned to appreciate in the quest for our own labs: What makes a research programme exciting and successful? How can you identify great places to apply to and make sure your application stands out? What are the key objectives for the job talk and the interview? How do you negotiate your position? And finally, how do you decide on a host institute that lets you develop both scientifically and personally in your new role as head of a lab?